Growth, mortality and recruitment of silver cyprinid (Rastrineobola argentea) in the open waters of Lake Victoria, Kenya. Issue 3 (3rd July 2018) - Yongo, Edwine; Manyala, Julius; Agembe, Simon
Abstract: This study investigated the growth, mortality and recruitment of Rastrineobola argentea in Lake Victoria on the basis of length–frequency data collected during the period 2014–2015. The asymptotic length ( L ∞ ) had a mean (± SE ) value of 53.50 ± 0.50 mm SL, growth curvature ( K ) of 0.81 ± 0.06 year −1, total mortality ( Z ) of 2.96 ± 0.12 year −1, a natural mortality ( M ) of 1.23 ± 0.06 year −1, a fishing mortality ( F ) of 1.74 ± 0.07 year −1, an exploitation rate ( E ) of 0.59 ± 0.01, a growth performance index ( ∅′ ) of 3.36 ± 0.02 and a length at 50% capture ( L 50 ) of 28.25 ± 0.43 mm SL. The fish exhibited a peak breeding during the months of May and August. The Beverton and Holt relative yield‐per‐recruit model indicated mean (± SE ) indices as 0.37 ± 0.01 for optimum sustainable yield ( E 0.5 ), 0.76 ± 0.01 for maximum sustainable yield ( E max ) and 0.66 ± 0.01 for economic yield ( E 0.1 ). Compared with previous studies, there is a great decline in the sizes of R. argentea stocks in Lake Victoria. Thus, management measures should include restriction on illegal seine nets <10 mm mesh size and re‐enforcement of a fishing ban or a closed season.